THE CORRECTION TECHNIQUES USED IN TEACHING DICTATION AT THE 3rd SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF TEACHER TRAINING AND EDUCATION FACULTY - Devie Reztia Anjarani; Evha Nazalatus Sy; Yuliarsih Yuliarsih; Rohmah Indahwati (Universitas Madura, 2020)
Dictation is one of techniques in learning foreign language. Understanding dictation is not always easy for students. An English lecturer should choose suitable techniques to teach them in order not to make students bored because she is one of the factors that determines whether the teaching learning process will be successful or not. The lecturer has to be able to apply various techniques in teaching English because the students prefer listening and writing an easy text. So, the lecturer can use correction techniques like shadow dictation and passing the buck.